2008
DOI: 10.1080/00224490802204431
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Experiences and Adult Health Sequelae Among Gay and Bisexual Men: Defining Childhood Sexual Abuse

Abstract: Gay and bisexual men carry the burden of HIV infections in the United States and have high rates of childhood sexual abuse that predict HIV and other health outcomes. This study examined differential effects of forced, consensual, and no childhood sexual experiences (CSE) on health outcomes among a probability sample of adult men who have sex with men (MSM). The forced sex group had the highest levels of psychological distress, substance use, and HIV risk. There were no differences in rates of depression and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 29 publications
10
90
0
2
Order By: Relevance
“…Care should be confidential, and it is not the role of the pediatrician to inform parents/guardians about the teenager' s sexual identity or behavior; doing so could expose the youth to harm. 88 …”
Section: Health Disparities For Transgender Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Care should be confidential, and it is not the role of the pediatrician to inform parents/guardians about the teenager' s sexual identity or behavior; doing so could expose the youth to harm. 88 …”
Section: Health Disparities For Transgender Youthmentioning
confidence: 99%
“…This negative interaction may then hinder the health care provider' s ability to form a trusting relationship. 88,102 Likewise, intake forms and questionnaires should not assume heterosexuality. Another advantage of altering intake forms is to be welcoming to parents who are in same-sex relationships.…”
Section: Making the Office Teen-friendly For Sexual Minority Youthmentioning
confidence: 99%
“…While the distinction between prepubertal children and those in puberty's earlier or later stages is not always made clear, this finding is supported for the former as well as the latter in both qualitative (Burns 2015;Leahy 1991Leahy , 1992Rivas 2013;Sandfort 1984) and quantitative research. Quantitative studies show that those childhood and adolescent 1 3 sexual experiences with adults that were retrospectively reported as having been consensual are not generally associated with negative outcomes (Arreola et al 2008;Carballo-Diéguez et al 2012;Constantine 1981;Coxell et al 1999;Dolezal et al 2014;Kilpatrick 1987Kilpatrick , 1992Sandfort 1992;Stanley et al 2004) and may be reported in very positive terms as relationships characterised by "warmth, pleasure, affection, humor, and even lustiness" (Okami 1991). Sometimes the child "victim" in cases that come to the attention of the authorities feels that that the law is oppressive and that the notional offender does not deserve to be treated as such (Leahy 1996).…”
Section: Perversion and Obscenitymentioning
confidence: 99%
“…There is a great deal of debate in the literature on child prostitution and child sexual exploitation as to whether or not a child is culpable with regard their decision to have sex for a price. Whilst some assert the child's culpability in this matter, it is also argued that saying that they choose to be exploited is a false premise, since they do not have the ability to make well-informed decisions that are rational and that they do not have the power to choose a different path for themselves (De Sas Kropiwnicki, 2012;Lutya, 2009;Areola et al, 2008).…”
Section: Theme 3: Adult Survivors' Accounts Of the Feelings And Emotimentioning
confidence: 99%